2023
DOI: 10.1002/adom.202202804
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chirality Transfer and Amplification from Chiral Cysteine to Gold Nanorod Assemblies using Nonchiral Surface Ligands

Abstract: Owing to large chiroptical activity and high tunability, dynamic chiral superstructures of plasmonic nanoparticles have attracted great attention. A useful strategy has been developed to obtain strong plasmonic chiroptical responses (plasmonic circular dichroism, PCD) by adding small chiral thiols on achiral side‐by‐side assemblies of gold nanorods (AuNRs). Despite the critical role of chiral thiols, the impact of achiral surface ligands is yet to be revealed. Herein, the effects of achiral surface ligands are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The high dependence of the etch pattern on Cys modification suggested that we may obtain Cys adsorption features by decoding the etch pattern. Previously, we found that in achiral side-by-side (SS) assemblies of AuNRs, introduction of chiral Cys could induce huge PCD signals. Particularly, we observed a volcano-like relationship between the PCD signal and Cys concentration. Notably, strong PCD responses were achieved at a low Cys amount with a narrow concentration window.…”
Section: Resultsmentioning
confidence: 66%
“…The high dependence of the etch pattern on Cys modification suggested that we may obtain Cys adsorption features by decoding the etch pattern. Previously, we found that in achiral side-by-side (SS) assemblies of AuNRs, introduction of chiral Cys could induce huge PCD signals. Particularly, we observed a volcano-like relationship between the PCD signal and Cys concentration. Notably, strong PCD responses were achieved at a low Cys amount with a narrow concentration window.…”
Section: Resultsmentioning
confidence: 66%